Adaptasi Tindakan Ekonomi Pelaku Sektor Pariwisata Pada Masa Pandemi Covid-19 - Ni Wayan Ayu Santi; Luh Indrayani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic that lasted more than a year had an impact on all levels of society, especially the tourism sector players in Bali Province. This study aims to determine the adaptation of the economic actions of tourism sector actors during the Covid-19 pandemic in Banjar Lodsema, Lodtunduh Village, Ubud District, Gianyar Regency, Bali Province. The research method is descriptive qualitative research. The subjects of this research are tourism sector actors in Banjar Lodsema while the object is the adaptation of economic actions taken by tourism sector actors during the Covid-19 pandemic. Data was collected by observation and interviews. The data that has been collected is analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that there is an adaptation of the economic actions of tourism sector actors in Banjar Lodsema, Lodtunduh Village, Ubud District, Gianyar Regency, Bali Province in the form of (1) actions prioritizing the fulfillment of primary needs, (2) maximizing the tourism sector business that is already owned, ( 3) opening a new business in the culinary field, (4) diversifying products, (5) maximizing the side business (online) that you already have, (6) looking for additional income such as being a laborer, (7) doing other businesses in agriculture and farms, and some (8) do forex trading.